Protocol for the Care-IS Trial: a randomised controlled trial of a supportive educational intervention for carers of patients with high-grade glioma (HGG). Issue 10 (26th October 2015) - Halkett, Georgia K B; Lobb, Elizabeth A; Miller, Lisa; Phillips, Jane L; Shaw, Thérése; Moorin, Rachael; Long, Anne; King, Anne; Clarke, Jenny; Fewster, Stephanie; Hudson, Peter; Agar, Meera; et al.
Abstract : Introduction: High-grade glioma (HGG) is a rapidly progressive and debilitating disease. Primary carers experience significant levels of distress which impacts on their experience of caregiving, the quality of care received and the community in terms of the increased reliance on healthcare due to the potential development of complicated grief. This paper describes the protocol for testing the efficacy and feasibility of an intervention for primary carers of patients with HGG in order to improve preparedness to care and reduce carer distress. Methods: Randomised controlled trial. The target population is carers of patients with HGG who are undergoing combined chemoradiotherapy. The intervention consists of 4 components: (1) initial telephone assessment of unmet needs of the carer, (2) tailoring of a personalised resource folder, (3) home visit, (4) ongoing monthly telephone contact and support for 12 months. The control arm will receive usual care. Primary hypothesis: This intervention will improve preparedness for caring and reduce carer psychological distress. Secondary hypothesis: This intervention will reduce carer unmet needs. The longer term aim of the intervention is to reduce patient healthcare resource utilisation and, by doing so, reduce costs. Assessments will be obtained at baseline, 8 weeks post intervention, then 4, 6 and 12 months. Participants will also complete a healthcare utilisation checklist and proxy performance status which will be assessed at baseline and monthly. 240 carers will be recruited. The sample size is 180. Multilevel mixed effects regression models will be applied to test the effect of the intervention. Ethics: Ethics approval has been gained from Curtin University and the participating sites. Dissemination: Results will be reported in international peer-reviewed journals. Trial registration number: Australian and New Zealand Clinical Trials Registration (ACTRN)12612001147875.